2016
DOI: 10.1080/03019233.2016.1229880
|View full text |Cite
|
Sign up to set email alerts
|

Peak load and energy absorption of DP600 advanced steel resistance spot welds

Abstract: The paper aims at investigating the microstructure, failure mode transition, peak load and energy absorption of DP600 dual phase steel during the tensile-shear test. It was found that the welding current has profound effect on the load-displacement characteristics. In the low welding current, welds failed in interfacial failure mode. Increasing welding current resulted in sufficient weld nugget growth to promote double-sided pullout failure mode with improved mechanical properties. Further increase in the weld… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 20 publications
1
14
0
Order By: Relevance
“…Microhardness and microstructural characteristics of the resistance spot weld joint are the key factors affecting their failure mechanism . Therefore, hardness variation across the joint is explained based on the microstructure development.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Microhardness and microstructural characteristics of the resistance spot weld joint are the key factors affecting their failure mechanism . Therefore, hardness variation across the joint is explained based on the microstructure development.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that hardenability of the intercritical austenite is higher compared to initial hardenability of the steel due to carbon partitioning during intercritical annealing. Austenite can transform into ferrite, pearlite, martensite, and bainite depending on the cooling rate and hardenability of steel .…”
Section: Resultsmentioning
confidence: 99%
“…Three samples are prepared for each run and out of these, two are used for the tensile shear test and one for metallurgical examination. Spot welded joint has more tendency to fail in the IF mode for the tensile shear test compared to other tests such as peel test and cross tension test [6,32]. Furthermore, it is observed that if spot weld joint fails in the pull-out failure (PF) mode during the tensile shear test, then it will also show failure behaviour with the PF mode during the peel test as well as the cross tension test [7]; therefore, the tensile shear test is carried out to investigate the mechanical performance of spot welded joint.…”
Section: Methodsmentioning
confidence: 99%
“…Jaber et al have found that the greater electrical current used than optimal might displace the location of the pressing force in 221 welding. There is presented a dependency of the electrical current and the displacement effect but it is limited for a specified work case given in the paper [6].…”
Section: Introductionmentioning
confidence: 99%